Social robot for older adults with cognitive decline: a preliminary trial - Figueroa, David; Yamazaki, Ryuji; Nishio, Shuichi; Maalouly, Elie; Nagata, Yuma; Satake, Yuto; Yamakawa, Miyae; Suzuki, Maki; Kanemoto, Hideki; Ikeda, Manabu; Ishiguro, Hiroshi (Frontiers in Robotics and AI, 2023)
The number of older adults living alone is rapidly increasing. Loneliness in older adults not only degrade their quality of life but also causes troubles such as heavy burden on the medical staff, especially when cognitive decline is present. Social robots could be used in several ways to reduce such problems. As a first step towards this goal, we introduced conversation robots into the homes of older adults with cognitive decline to evaluate the robot's availability and acceptance during several months. The study involved two steps, one for evaluating the robustness of the proposed robotic system, and the second one to examine the long-term acceptance of social robots by older adults with cognitive decline living alone. Our data shows that after several weeks of human-robot interaction, the participants continued to use the robot and successfully integrated them into their lives. These results open the possibility of further research involving how sustained interaction can be achieved, as well as which factors contributed to the acceptance of the robot.